2017
DOI: 10.2141/jpsa.0170001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Inclusion of Lemon Balm (<i>Melissa Officinalis </i>L.) Extract on Performance, Gut Microflora, Blood Parameters, Immunity and Carcass Traits of Broilers

Abstract: The aim of the present study was to evaluate the effects of lemon balm (LB; Melissa officinalis L.) extract as additive on performance, health status and carcass traits of broilers during a 42-days production cycle. One hundred mixed chicks of Ross 308 strain were assigned for five dietary treatments with four replicates per group and five birds per replicate as follows: control diet, 0.5LB, 1.0LB, 1.5LB and 2.0LB with 0.0, 0.5, 1.0, 1.5 or 2.0 mL of LB extract per liter of drinking water, respectively. In ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…Interestingly, the performance of these chickens was improved during the grower phase with also a trend for a lower occurrence of muscle defects. These effects of MEL extract supplementation on chicken performance have been described previously (20,21) and are strengthened by our study. The beneficial antioxidative activity of MEL was also reported on the quality of meat by limited lipid oxidation (20).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, the performance of these chickens was improved during the grower phase with also a trend for a lower occurrence of muscle defects. These effects of MEL extract supplementation on chicken performance have been described previously (20,21) and are strengthened by our study. The beneficial antioxidative activity of MEL was also reported on the quality of meat by limited lipid oxidation (20).…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, few studies have demonstrated and documented the capacity of MEL extract to improve the defense system of chickens and its impact on their health, welfare and performance (20,21). The different steps reported in this study range from the quality of MEL extract, its possible cytotoxicity on chicken cell lines and its potential to stimulate immune functions in vitro, the capacity to reveal its antioxidative and anti-inflammatory properties in an original ex vivo model of inflammation to the assessment of its effects on welfare, health and performance indicators in chickens reared in suboptimal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Mehr et al (2014) found that dietary inclusion of clove oil at 0.15, 0.30 g/kg did not affect antibody titers against NDV and avian influenza in broiler chickens. Moreover, Poorghasemi et al (2017) reported that antibody titers against NDV and IBDV were not affected by dietary lemon balm supplementation in broiler chickens. Additionally, Toghyani et al (2011) stated that antibody titers against avian influenza virus and NDV were not significantly different in broiler chickens fed diets supplemented with 2 g/kg and 4 g/kg of cinnamon bark powder.…”
Section: Resultsmentioning
confidence: 99%
“…The total weight of all dissected organs was also calculated. Ratios were calculated according to the following formula: [(weight of component(s)/eviscerated carcass weight) Â 100] (Poorghasemi et al 2017). Carcass components, gastrointestinal organs and heart were measured according to the methods described by Seidavi et al (2014) on 42 nd day of age.…”
Section: Measured Variablesmentioning
confidence: 99%